Authenticity in islamic sacred spaces: Case studies of distinctive regional mosques - Husni, Muhammad Fahd Diyar (Institute for Advanced Science, Social, and Sustainable Future, 2024)
This paper delves into the authenticity of Islamic sacred spaces through an architectural and cultural examination of distinctive regional mosques, specifically Bait Ur Raiyan Mosque, The Mamluki Lancet Mosque, and mosques in Sub-Saharan Africa. By exploring these mosques as case studies, the research aims to highlight the unique aspects of Islamic architectural authenticity that reflect the cultural, historical, and regional diversities within the Islamic world. Utilizing a comparative analysis method, the study investigates the architectural elements, design principles, and contextual significance that contribute to the mosques' authenticity. The findings reveal that despite geographical and cultural variances, these mosques share a common commitment to Islamic architectural traditions while also adapting to local influences and needs. This study underscores the importance of preserving architectural authenticity in maintaining the cultural and religious identity of Islamic sacred spaces. It contributes to a broader understanding of how Islamic architecture has evolved across different regions, offering insights into the delicate balance between tradition and innovation in the construction of sacred spaces.